Medication adherence and relapse in patients with schizophrenia: A literature review - Rahmanda Putri, Venna; Carolia, Novita; Islami, Suryadi; Septa, Tendry (JOURNAL OF Mental Health Concerns, 2026)
Background: Schizophrenia is a chronic psychiatric disorder with high relapse rates that significantly affect social functioning, quality of life, and healthcare burden. Medication adherence to antipsychotic treatment plays a critical role in maintaining clinical stability and preventing relapse; however, it remains a major challenge in clinical practice. Purpose: To examine the relationship between medication adherence and relapse among patients with schizophrenia through a narrative review approach. Method: Literature searches were conducted in Google Scholar, PubMed, NCBI, ScienceDirect, and Elsevier between January and February 2024 using keywords related to medication adherence, schizophrenia, and relapse. Of the 85 identified articles, 8 studies met the inclusion criteria and were analyzed narratively. Results: The review findings consistently demonstrated that non-adherence to antipsychotic medication was associated with a significantly higher risk of relapse, rehospitalization, and poorer long-term prognosis. Additionally, considerable variability was observed in the definitions and assessment methods of adherence and relapse across studies. Conclusion: Medication adherence is a key determinant in relapse prevention among patients with schizophrenia and should be a primary focus of long-term clinical management. Keywords: Medication Adherence; Relapse; Schizophrenia.